2011
DOI: 10.1128/aem.00365-11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental and Genetic Factors Linked to Celiac Disease Risk on Infant Gut Colonization by Bacteroides Species

Abstract: Celiac disease (CD) is an immune-mediated enteropathy involving genetic and environmental factors whose interaction might influence disease risk. The aim of this study was to determine the effects of milk-feeding practices and the HLA-DQ genotype on intestinal colonization of Bacteroides species in infants at risk of CD development. This study included 75 full-term newborns with at least one first-degree relative suffering from CD. Infants were classified according to milk-feeding practice (breast-feeding or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 29 publications
(29 reference statements)
2
82
0
4
Order By: Relevance
“…Our study demonstrated that B. uniformis CECT 7771 induced low TNF-a production and the highest IL-10 production in comparison with other strains of Bacteroides spp. Our recent studies also demonstrated that the prevalence of B. uniformis CECT 7771 in the gut of infants is favoured by breast-feeding [22] and breast-feeding seems to protect against later development of obesity as compared to formula feeding [34][35]. Considering these data altogether led us to hypothesise that the oral administration of B. uniformis CECT 7771 could exert beneficial effects in an obesity model as reported in this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our study demonstrated that B. uniformis CECT 7771 induced low TNF-a production and the highest IL-10 production in comparison with other strains of Bacteroides spp. Our recent studies also demonstrated that the prevalence of B. uniformis CECT 7771 in the gut of infants is favoured by breast-feeding [22] and breast-feeding seems to protect against later development of obesity as compared to formula feeding [34][35]. Considering these data altogether led us to hypothesise that the oral administration of B. uniformis CECT 7771 could exert beneficial effects in an obesity model as reported in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Individual colonies were isolated from the highest dilution plate from each subject and their cellular morphology and Gramstaining characteristics were examined. The isolated clones were identified at species level by sequencing of amplified 16S rDNA regions with the primers 27f and 1401r as previously described [22]. The PCR products obtained were purified using the GFXtm PCR DNA and Gel Band DNA Purification Kit (GE Healthcare, Buckinghamshire, UK) for DNA sequencing.…”
Section: Bacterial Strain and Culture Conditionsmentioning
confidence: 99%
“…33 Differences in the microbiota composition between formula-fed and breastfed infants have been shown, which might involve an increased celiac disease risk because differences in gut microbiota between individuals with and without celiac disease have been reported. 34,35 Furthermore, breastfeeding has been associated with a reduced risk of gastrointestinal infections, 29 an additional risk factor for celiac disease. 36 Age at gluten introduction might be important because it influences the proportion of infants still breastfed at that time and/or there might be a certain age interval that provides a "window of opportunity" with respect to developing oral tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…composition in early-life microbiota have been reported in infants with high genetic risk for CD development compared to infants with low genetic risk (163) . In detail, Bacteroides uniformis, B. ovatus and B. plebeius were associated with a low genetic risk, whereas B. vulgatus seems to be more prevalent both in high-risk infants (165) and in infants with active CD (153) . Furthermore, B. fragilis has been associated with an increased risk for CD development in genetically predisposed infants who were formula-fed (166) .…”
Section: Coeliac Diseasementioning
confidence: 99%